101 Case report: to stent, or not to stent? The pale cast of evidence-based practice in acute stroke. (29th July 2019) - Blair, Chris; Bhatia, Kartik; Brunacci, David; Worthington, John; Ahmed, Rebekah
Abstract : Introduction: With approximately 200 procedures performed in the last year at our centre, worthwhile clinical lessons continue to emerge in the practice of endovascular clot retrieval (ECR) for acute stroke. This case demonstrates the value of considered clinical appraisal in a dynamic, information-rich setting. A 68 year-old man with established vertebrobasilar atherosclerotic disease developed capricious, blood pressure-sensitive neurological deficits after successful ECR for a basilar artery stroke, inviting the possibility of further intervention in the form of intracranial stenting. We avoided pursuing this course of action in favour of a more measured approach, entailing the provision of vasopressor support over the following week. Method: Following ECR, our patient was admitted to the intensive care unit for continuous blood pressure monitoring and close observation of his neurological deficits with serial NIHSS (National Institutes of Health Stroke Scale) scoring. Systolic blood pressures were maintained between 140–160 mmHg using vasopressor support, with the aim of allowing time for recovery of vascular autoregulation and collateralization. Results: Over six days, the patient developed moderate left upper and lower limb weakness. An MRI performed on Day 5 revealed limited interval infarction of the right hemipons and cerebellum, with complete re-occlusion of the mid-basilar arterial segment. He left the ICU with a NIHSS score of 7, and was living independently at 90-day follow-up (Modified Rankin Score 1). Conclusion: The ultimately favourable net outcome for our patient clearly illustrates the imperative to remain within the boundaries of evidence-based practice in this bold and rapidly evolving discipline.